Complicated Appendicitis Among Adults With and Without Disabilities: A Cross-Sectional Nationwide Study in South Korea - Yeob, Kyoung Eun; Kim, So Young; Park, Jong Eun; Park, Jong Hyock (Frontiers in Public Health, 2022)
Objective Appendicitis is usually diagnosed based on a reliable set of signs and symptoms, and can be effectively treated with surgery, with low morbidity and mortality rates. However, appendicitis is often overlooked in vulnerable populations, including people with disabilities. This study compared 10-year trends of complicated appendicitis between South Koreans with a disability, according to disability severity and type, and those without disabilities Methods To identify cases of appendicitis, we used the DRG codes in the National Health Information Database of South Korea. Patients with appendicitis were classified in terms of severity based on the DRG codes. Age-standardized incidence rates were calculated for each year during 2008–2017 according to the presence, type, and severity of the disability. Factors associated with complicated appendicitis were examined by multivariate logistic regression using the most recent data (i.e., 2016–2017). Results The incidence of complicated appendicitis was higher in people with disabilities, especially those with severe disabilities (26.9 vs. 11.6%). This difference was particularly marked when considering those with a severe disability (aOR = 1.868, 95% CI:1.511–2.309), internal organ problems (aOR = 10.000, 95% CI:5.365–18.638) or a mental disability (aOR = 2.779, 95% CI:1.563–4.939). Conclusions The incidence of complicated appendicitis was higher in people with disability than in those without disability in all years. There was a substantial difference in the incidence of complicated appendicitis between the severe disability and non-disabled groups. Among the various disability types, the incidence of complicated appendicitis was highest for major internal organ problems, followed by intellectual or psychological disabilities. Our findings may be explained by barriers to healthcare access among people with disabilities, particularly those with a severe disability, internal organ problem, or mental disability.